Black Cumin: A Review of its Pharmacological Effects and its Main Active Constituent - Nyemb, Jean Noël; Shaheen, Hazem; Wasef, Lamiaa; Nyamota, Richard; Segueni, Narimane; Batiha, Gaber El-Saber (Pharmacognosy Reviews)
Black cumin (Nigella sativa) is a well-known medicinal plant and the most exhaustively exploited species of Ranunculaceae family. Nigella sativa seeds have been extensively used as spice in Middle Eastern and Indian cuisine. In addition, they have a long history of use in medicine. This review described the pharmacognostical characteristics, traditional applications and health benefits of N. sativa. The review also described the phytochemical composition and pharmacological properties of N. sativa and its bioactive constituents, in particular thymoquinone, the most abundant active constituent responsible of the effectiveness and pharmacological properties of N. sativa. The review also enumerates pharmacokinetics, possible interaction caused by co-administered drugs, daily dose consumption and toxicity of this medicinal plant. These make the use of N. sativa an interesting approach to the development of new adjuvant or complement treatment.
Keywords: N. sativa; Thymoquininone; Phytochemical composition; Pharmacological properties; Toxicity